Karakteristik Pasien Tuberkulosis Di Puskesmas Kauman Kabupaten Ngawi - Agung Wahyu Hidayat; Chintia Dyah Ayuning Putri (Consilium Sanitatis: Journal of Health Science and Policy, 2023)
Objective: The objective of this research is to identify the characteristics of Tuberculosis (TB) patients at the Kauman Public Health Center. Methods: This research employed an analytical descriptive methodology and analyzed patient medical records from 2020 to 2022 as well as data from SITB. In this research, 42 patients made up the sample. Results: The results showed that of the 42 patients with TB, 60% were male, and 40% were female. The age range of most TB sufferers is 45-60 years (36%), while the lowest is the age range 0-18 (7%). Most TB cases were new (98%) compared to those with a history of previous TB (2%). TB patients who are sensitive to drugs are 93%, while those who are not are only 7%. And the diagnosis of Lung TB (93%) is the majority compared to Extra Lung TB, only 7%. Conclusion: The results showed that most TB patients were male (60%), the age range of most TB patients was 45-60 years (36%), most TB cases were new (98%), most TB patients were drug-sensitive (93%), and the diagnosis the most was lung TB (93%). This research suggests that further research be carried out to discover other characteristics of TB patients with a larger sample size and more complex research methods.